2009
DOI: 10.1007/s00464-009-0829-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on outcomes of laparoscopic surgery for colorectal cancer in Asians

Abstract: With sufficient experience, laparoscopic colorectal surgery in obese Asian patients is feasible and safe, offering all the benefits of a minimally invasive approach. Management of Asian colorectal cancer patients with BMI > or = 30 kg/m(2) requires meticulous perioperative care, and colorectal surgeons must be familiar with obesity-related challenges in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 26 publications
0
102
1
1
Order By: Relevance
“…Of these studies, 12 were excluded for various reasons: 3 used other variable definitions of obesity [2,12,13]; 5 compared outcomes in tertiles or quartiles of BMI [14][15][16][17][18]; 1 evaluated the clinical outcomes of patients with morbidly obese [19]; and 2 were review [1,20]. In total, eight observational studies published between 2002 and 2009 matched the inclusion criteria and were therefore included [4-9, 21, 22].…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Of these studies, 12 were excluded for various reasons: 3 used other variable definitions of obesity [2,12,13]; 5 compared outcomes in tertiles or quartiles of BMI [14][15][16][17][18]; 1 evaluated the clinical outcomes of patients with morbidly obese [19]; and 2 were review [1,20]. In total, eight observational studies published between 2002 and 2009 matched the inclusion criteria and were therefore included [4-9, 21, 22].…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…There are several studies documenting the increased surgical complication risk in major abdominal and cardiac surgery in obese patients [3][4][5]. However, the role of obesity on cervical endocrine procedures has been much less investigated [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Only the age value showed compatibility with normal distribution within the groups, data of other variables were detected as out of normal distribution within the groups. Data concerning the age variable compatible with normal distribution were analyzed by one-way ANOVA and Turkey's HSD Post-hoc procedures, especially in major abdominal surgeries such as colectomy or pancreaticoduodenectomy [3][4][5]. There are some recent reports associated with the risk of morbidity and mortality also in parathyroid surgery [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Obstacles to performing laparoscopic surgery in obese patients include difficulties in obtaining an adequate operative field and difficulties in the intraabdominal maneuvering of instruments in a restricted working area. 2,16 These difficulties may also affect oncologic outcomes following colorectal cancer. However, this study showed no adverse effect of obesity on survival following laparoscopic colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of short-term outcomes, several studies have shown that obese patients have unfavorable surgical outcomes, such as longer operative times, increased conversion rates, increased postoperative complication rates, and prolonged hospital stays. [1][2][3] These unfavorable short-term outcomes may affect long-term outcomes for obese patients with colorectal cancer. However, some studies in Western patients showed that long-term outcomes for obese patients were not different from those for non-obese patients.…”
Section: Discussionmentioning
confidence: 99%